Influence of integrated nutrient management on productivity and quality of groundnut in Western Rajasthan - Ola, Bajrang Lal; Pareek, B. L.; Yadav, R. S.; Shivran, A. C.; Sharma, O. P. (Annals of Agricultural Research, 2014)
A field experiment in factorial randomized block design with three replications; using seed rate 80 kg/ha was conducted during kharif 2011 to study the effect of integrated nutrient management in groundnut (variety ’HNG-10’). Application of FYM @ 8 t/ha + 50% RDF produced significantly higher yield, oil content, oil yield and protein content as well as N, P content and uptake by groundnut but remained at par with vermicompost @ 3 t/ha + 50% RDF. However, Rhizobium and PSB proved equally good but superior to control in respect to yield, oil content, oil yield and protein content as well as N, P content and uptake.